(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The purpose of this research is to investigate the creation, properties, and potential applications of inclusion complexes of hydroxypropyl-β-cyclodextrin (HP-β-CD) with certain medicines and fluorophores. There has been interest in cyclodextrins—cyclic oligosaccharides that may form host-guest complexes—because of their capacity to improve the bioavailability, stability, and solubility of chemicals that are not very water-soluble. An excellent encapsulating agent is hydroxypropyl-β-cyclodextrin, a modified derivative of β-cyclodextrin that has decreased toxicity and better water solubility. The researchers in this study used kneading and co-precipitation techniques to combine HP-β-CD with fluorescent dyes and medicinal drugs. Fluorescence time-of-flight (FTIR), differential scanning calorimetry (DSC), powder X-ray diffraction (PXRD), and ultraviolet-visible spectroscopy were used to characterise the resultant complexes and validate their synthesis, as well as to study physicochemical alterations. With their improved drug solubility and photostability of fluorophores, the inclusion complexes showed promise for drug delivery and biomedical imaging. Molecular docking simulations provide shed light on the guest-host molecules’ structural compatibility and interaction processes. This research highlights the adaptability of HP-β-CD as a supramolecular carrier in analytical and pharmaceutical chemistry, opening up new possibilities for the creation of stable and more efficient formulations of molecules with therapeutic and diagnostic value.